2019
DOI: 10.1007/s00520-019-04802-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for febrile neutropenia in Japanese patients with non-Hodgkin B cell lymphoma receiving R-CHOP: 2-year experience in a single center (STOP FN in NHL 2)

Abstract: Background Myelosuppressive chemotherapy-induced febrile neutropenia (FN) is a life-threatening condition. Patients receiving granulocyte colony-stimulating factors (G-CSF) have shorter duration of neutropenia, faster recovery from fever, and shorter duration of antibiotics use. Most strategies for FN prevention using daily G-CSF and pegfilgrastim are based on overseas studies. Data on Japanese patients were lacking; thus, we previously determined the incidence of FN in non-Hodgkin B cell lymphoma (B-NHL) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
6
3
Order By: Relevance
“…The incidence of grade ≥3 neutropenia and febrile neutropenia seen in our study was 13% and 9%, respectively, which is lower when compared with reported studies ( 31 ). This may be because our patient population is predominantly younger and the majority present with good risk International Prognostic Index score.…”
Section: Discussioncontrasting
confidence: 85%
“…The incidence of grade ≥3 neutropenia and febrile neutropenia seen in our study was 13% and 9%, respectively, which is lower when compared with reported studies ( 31 ). This may be because our patient population is predominantly younger and the majority present with good risk International Prognostic Index score.…”
Section: Discussioncontrasting
confidence: 85%
“…The proportion of very elderly patients who developed FN tended to be lower than the proportions in previous studies involving younger patients. 6,11,12 There are several possible reasons for the lower incidence of FN in the present study compared with the previous studies, despite the older age of the patients and the lower percentage of prophylactic G-CSF use. One reason may be the high proportion of patients with reduced chemotherapeutic dose in the present study.…”
Section: Risk Of Febrile Neutropenia In Very Elderly Patients Aged ≥8...contrasting
confidence: 53%
“…This nationwide analysis revealed the features of FN among very elderly patients with DLBCL, which remained to be well established. The proportion of very elderly patients who developed FN tended to be lower than the proportions in previous studies involving younger patients 6,11,12 …”
Section: Characteristics Patients Aged ≥80 Years N = 1819mentioning
confidence: 57%
“…A previous study has reported that pre-existing anemia may increase the risk of developing FN or severe neutropenia in patients treated with chemotherapy [28]. Lower levels of hemoglobin are associated with myelosuppression, which can further exacerbate the condition and lead to a higher incidence of FN [29]. This may explain why basal Hb < 12 g/dL increases the incidence of grade 4 neutropenia.…”
Section: Discussionmentioning
confidence: 97%